2013
DOI: 10.5194/cp-9-499-2013
|View full text |Cite
|
Sign up to set email alerts
|

Paleohydrology reconstruction and Holocene climate variability in the South Adriatic Sea

Abstract: Abstract. Holocene paleohydrology reconstruction is derived combining planktonic and benthic stable oxygen and carbon isotopes, sea surface temperatures (SSTs) and oxygen isotope composition of seawater (δ18Ow) from a high sedimentation core collected in the South Adriatic Sea (SAS). Core chronology is based on 10 AMS 14C measures on planktonic foraminifera and tephra layers. Results reveal two contrasted paleohydrological periods that reflect (i) a marked lowering of δ18Ow/salinity during the early to mid-Hol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 114 publications
8
43
0
Order By: Relevance
“…It has been shown that the most productive months of G. bulloides in the Mediterranean Sea are April-May (Pujol and Vergnaud Grazzini, 1995). A complete description of δ 18 O measurements can be found in Siani et al (2013) for core MD90-917 and in Essalami et al (2007) for core MD04-2797.…”
Section: Oxygen Isotopesmentioning
confidence: 99%
“…It has been shown that the most productive months of G. bulloides in the Mediterranean Sea are April-May (Pujol and Vergnaud Grazzini, 1995). A complete description of δ 18 O measurements can be found in Siani et al (2013) for core MD90-917 and in Essalami et al (2007) for core MD04-2797.…”
Section: Oxygen Isotopesmentioning
confidence: 99%
“…7f) suggests that the African lakes were more affected by the climatic oscillation around 7500 cal BP than the Mediterranean ones, while they show nearly synchronous rises in water table around 10 500 cal BP. In the northern Mediterranean (Lake Accesa) and in west-central Europe (Lake Cerin), the period around 7500 cal BP coincided with the beginning of a trend toward higher lake-level conditions, while marine core MD90-917 in the southern Adriatic Sea shows a marked decline in salinity around 7500-7000 cal BP probably due to increased discharge from the Po River in northern Italy Siani et al, 2013).…”
Section: Climmentioning
confidence: 99%
“…In core MD90-917, Siani et al (2010Siani et al ( , 2013 have identified several tephras of interest for correlation between tephro-and climato-stratigraphies (Fig. 5).…”
Section: Climato-and Tephro-stratigraphiesmentioning
confidence: 99%
“…The initial reduction in 14 C dates coincides with a significant decline in sea surface temperatures (SST) in the southern Adriatic between 7800 and 7500 cal BP. This was followed by a more pronounced SST cooling between 7300 and 6300 cal BP, which at its nadir was characterized by SSTs lower than those registered during the 8.2 ka event (Siani et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Cumulative calibrated dating probability of radiocarbon data (terrestrial series) from Mesolithic and Early Neolithic sites along the Danube main channel in the Iron Gates, compared to climate proxy records from the North Atlantic and Europe 10,000-6000 cal BP. A -after Bond et al (1997); B, D, F, G -smoothed records redrawn from Rohling and Pälike (2005); E -after Siani et al (2013); C -horizontal bars represent cold phases recorded in δ 18 O records from V11 Cave, NW Romania (Tămaș et al, 2005) and Katerloch Cave, Austria (Boch et al, 2009); vertical grey bars represent higher lake-level events in the Alps-Jura region (Magny, 2004). (Wurth et al, 2004); 2 -Katerloch Cave (Boch et al, 2009); 3 -V11 Cave (Tămaș et al, 2007); 4 -Lake Ammersee (von Grafenstein et al, 1998(von Grafenstein et al, , 1999; 5 -Lake Schleinsee (Tinner and Lotter, 2001); 6 -Lake Soppensee (Tinner and Lotter, 2001); 7 -Brunnboden and Krummgampen peat bogs (Kofler et al, 2005); 8 -Preluca Tiganului and Steregoiu peat bogs (Feurdean, 2005); 9 -Alps-Jura lakes study region (Magny, 2004); 10 -Teleorman Valley (Macklin et al, 2011); 11 -Durance Valley (Miramont et al, 2001); 12 -Middle Rhône Valley (Berger et al, 2002).…”
Section: Fig 1 Mesolithic and Early Neolithic Sites In The Ironmentioning
confidence: 99%